Understanding weight regain: Insights from Saudi patients on factors influencing post-metabolic and bariatric surgery outcomes: A qualitative study - Suhair Al-Ghabeesh; Ahmad Rayan; Enas A. Assaf; Mirna Fawaz; Abbass AlBay; Hanan Alyami (PLoS ONE, 2026)
Background Weight restoration is still possible even if Metabolic and Bariatric Surgery is the most efficient therapy for extreme obesity. While the non-controllable causes of weight regain have been investigated, the controllable causes of weight regain have received less attention. Purpose The aim of this study was to explore the factors contributing to weight regain after Metabolic and Bariatric Surgery as perceived by patients. Methods A qualitative descriptive research design used, where semi-structured interviews were carried out. Results The thematic analysis gave rise to five themes. The first theme was titled “Economic challenges,” and it highlighted the challenges experienced by the patients in maintaining a healthy diet. The second theme, “Emotional instability and occupational stress,” reflects the psychological concerns that patient’s experience, which hinder them from keeping a healthy lifestyle. The “Social influence” theme focused on the environment of the patients, which enhanced cravings, and the “Lack of support” theme highlighted the negative perspective of the social network of the participants towards the patients’ surgery and desired lifestyle. Finally, the “False beliefs and decreased physical activity” theme focused on how the perception of the patients towards the results or effects of the surgery led to reduced physical activity, which they perceived as leading to weight gain. Conclusion Despite being successful, weight regain can still happen following bariatric surgery. In order to promote long-term weight loss sustainability, the results of this paper reinforce the idea that persons who have had Metabolic and Bariatric Surgery ought to be educated of the controllable variables linked with weight rebound, future research address the long term effect and the weight control factors following the surgery are highly recommended.